2012
DOI: 10.1152/japplphysiol.00768.2011
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric changes in the human pulmonary acinus during inflation

Abstract: Despite decades of research into the mechanisms of lung inflation and deflation, there is little consensus about whether lung inflation occurs due to the recruitment of new alveoli or by changes in the size and/or shape of alveoli and alveolar ducts. In this study we use in vivo (3)He lung morphometry via MRI to measure the average alveolar depth and alveolar duct radius at three levels of inspiration in five healthy human subjects and calculate the average alveolar volume, surface area, and the total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 33 publications
7
70
0
Order By: Relevance
“…Endoscopic confocal microscopy (50) has been used to track alveolar expansion in mouse lungs and has shown evidence of alveolar recruitment driven by airflow between alveoli via the pores of Kohn (40). 3 He-diffusion MRI studies of healthy human lungs suggest inflation occurs primarily through recruitment in conjunction with anisotropic expansion of the alveolar ducts (18). We propose that OCT needle probes provide an alternative imaging modality to explore the specific mechanisms of lung inflation (i.e., alveoli expansion vs. recruitment).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Endoscopic confocal microscopy (50) has been used to track alveolar expansion in mouse lungs and has shown evidence of alveolar recruitment driven by airflow between alveoli via the pores of Kohn (40). 3 He-diffusion MRI studies of healthy human lungs suggest inflation occurs primarily through recruitment in conjunction with anisotropic expansion of the alveolar ducts (18). We propose that OCT needle probes provide an alternative imaging modality to explore the specific mechanisms of lung inflation (i.e., alveoli expansion vs. recruitment).…”
Section: Discussionmentioning
confidence: 97%
“…Intravital (26) and confocal microscopy (44) have been used with some success to image alveoli in rats. However, this is restricted to imaging alveoli at the very surface of the lung due to the limited penetration depth of these imaging modalities, in the latter case to a depth of 30 m. Other more indirect approaches have also been applied, notably 3 He diffusion magnetic resonance imaging (MRI) (18), which provides estimates of alveolar volume and surface area by characterizing the pattern of 3 He diffusion through the lungs and combining this with geometrical models of idealized alveolar ducts. These techniques are noninvasive and lend themselves to dynamic studies, although the limited spatial resolution of the underlying MRI acquisitions means that these measurements are not able to image individual alveoli.…”
mentioning
confidence: 99%
“…Measurements of 3 He ADC have been widely recognized as accurate and precise biomarkers of airspace enlargement (27,28,41,42), and elegant mathematical models of gas diffusion in alveolar ducts have led to refined understanding of parenchymal microstructure and alveolar recruitment (43)(44)(45). Our validation in explanted lungs, and in vivo MR imaging measurements by others (30,34), demonstrate that 129 Xe diffusion MRI can be used as a similar biomarker of airspace enlargement (46) ¼ 6.4ms is necessary to adequately sample the local environment for restricted xenon diffusion; this criterion thus ensures maximal contrast between control and emphysematous tissue.…”
Section: Direct Comparison Ofmentioning
confidence: 99%
“…The soft tissue density is q s ¼ 1000 kg=m 3 , the tissue bulk modulus is taken to be that of the water as K s ¼ 2.2 GPa [49]. Air viscosity at 20 C is l f ¼ 1:82 Â 10 À5 Pa Á s. The [46,50] demonstrated that the alveolar duct radius of both human and dog lung increases with pressure. As the weight of the pig used in this experiment was close to that of the dog, we took the alveolar duct radius as 0.225 mm at 20 cm H 2 O and 0.2 mm at 10 cm H 2 O, which are within the range of the measurements made by Hajari.…”
Section: Resultsmentioning
confidence: 99%